Extension of the diet of an extreme foraging specialist, the aardwolf (Proteles cristata) - de Vries, J.; Pirk, C.; Bateman, Bill; Cameron, E.; Dalerum, F. (Universiteit Stellenbosch * Department of Botany and Zoology, 2011)
The aardwolf, Proteles cristata, is a highly specializedmyrmecophagous carnivore that feeds almost exclusivelyon termites of the genus Trinervitermes. Herewe report data from an ongoing analysis of aardwolfdiet, where we documented remains of sun spidersand scorpions in aardwolf scats. Although the prevalenceof these items was low, with sun spiders recordedin nine and scorpion remains in one of 246 scats, ourobservations suggest that aardwolves opportunisticallyfeed on larger prey than previously thought.However, our observations do not suggest thataardwolves utilized these large prey items as alternativesto their main food resource during periods offood scarcity. Therefore, we suggest that the adaptiveadvantages of such opportunism may be small, butthat the observed behavioural plasticity could beadvantageous under specific environmental conditionsand therefore is maintained as a behavioural trait.